Commitment and Matching Contributions to Public Goods - Robin Boadway; Zhen Song; Jean-Francois Tremblay (Queen's University, Department of Economics, 2006)
This paper studies multi-stage processes of non-cooperative voluntary provision of public goods. In the first stage, one or more players announce contributions that may be conditional on the subsequent contributions of others. In later stages, players choose their own contributions and fulfill any commitments made in the first stage. Equilibrium contributions are characterized under different assumptions about the commitment ability of players, the number of public goods and whether players commit to matching rates or to discrete quantities. We focus on contribution mechanisms that can emerge and be sustainable without a central authority, and that therefore may be particularly relevant for the provision of international public goods. Efficient levels of public goods can be achieved under some circumstances.
Keywords: H41; H87; 330; voluntary provision; matching contributions; commitment; multiple public goods